Masyarakat dan Lingkungan Pendidikan Perspektif Ibnu Khaldun - Febby Erika; Raihana Aulia Sukhairani; Supardi Ritonga; Endy Dharma Pangestu; M. Zakariya Al Ansori (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine Ibn Khaldun's views on society and the educational environment and their relevance to education in contemporary Indonesia. A qualitative approach was used through literature review, analyzing books, journals, and articles related to Ibn Khaldun's thoughts on education and civilization. The results indicate that Ibn Khaldun viewed education as a means of developing the whole person, encompassing moral, intellectual, social, and practical skills. He emphasized the importance of integrating religious and rational knowledge, gradual learning methods (tadrīj) and repetition (takrīr), and education adapted to the social and cultural conditions of society. These ideas are relevant to modern Indonesian education, particularly in the development of a holistic curriculum, character formation, and the enhancement of students' practical skills.